Situation of Postpartum Maternity Blues - Mangkhang, Wasana; Yotsena, Benchamat; Pupjain, Srijan (Journal of Health Science of Thailand, 2019)
This research aimed to study the meaning and the situation of maternity blue, a form of postpartum depression, through literature review of academic publications and original articles relating to postpartum care. Data were collected and analyzed in order to generate definition and meaning of the “blues”. Furthermore, factors affected to emotion of mother during puerperium period were also investigated in this study. It was found that the “blues” was deswcribed as a state of emotional disorders which could be observed in women during the first year of the postpartum period. The main characteristics of disorder included depression, drowsiness, mood swings, irritability, tiredness, insomnia, fatigue, feeling desperate, pessimistic anorexia, lack of self-interest and having suicidal thought. Due to biological, physiological and social stress, these circumstances could lead to the change in the mother behaviors.